Coordinated kinetics of humoral, T-cell, and cytokine responses to SARS-COV-2 in West African healthcare workers: a multicenter longitudinal study in university hospitals of Abidjan, Côte d’Ivoire - Goran-Kouacou, Amah Patricia Victorine; Yéboah, Oppong Richard; Séri, Yida Jocelyne; Assi, Aya Ursule Aniela; Adou, Adjoumanvoulé Honoré; Moussa, Salimata; Oura, Brou Doris; N’Guessan, Koffi; Siransy, Kouabla Liliane; Dassé, Séry Romuald (Frontiers in Immunology, 2025)
BackgroundHealthcare workers in resource-limited settings are frequently exposed to SARS-CoV-2, often with incomplete vaccine coverage. Yet, their adaptive immune responses remain poorly characterized in sub-Saharan Africa.MethodsWe conducted a multicenter study involving 36 healthcare workers with RT-PCR-confirmed SARS-CoV-2 infection (83.3% vaccinated) and 40 strictly unvaccinated, COVID-19-naïve controls from three university hospitals in Abidjan. Blood samples were collected on Days 0, 7, 14, 21, and 28. IgM and IgG were measured by ELFA (Mini VIDAS®), neutralizing antibodies with CHORUS TRIO®, lymphocyte subsets by flow cytometry, and Th1/Th2/Th17 cytokines using bead-based multiplex assays.ResultsInfected participants showed strong antibody production at baseline. IgG levels were closely linked to neutralizing activity (ρ = 0.83; p < 0.0001), and CD4+ T-cell counts correlated with IL-2 (ρ = 0.71; p < 0.0001). We observed early activation across Th1 (IFN-γ, TNF-α), Th2 (IL-4, IL-10), and Th17 (IL-17A) pathways. IL-17A levels were higher in asymptomatic individuals (p = 0.031). Over time, IgM and pro-inflammatory cytokines declined, while IgG remained stable and regulatory cytokines rose.ConclusionThis cohort developed a broad immune response involving antibodies, T cells, and cytokines. The IL-17A pattern seen in asymptomatic cases may reflect effective mucosal control. These findings contribute essential data from a region where immune profiling remains limited.